CS-27 Mortality among patients with systemic lupus erythematosus hospitalized with sepsis varies widely among U.S. hospitals. (August 2018) - Ward, Michael M; Tektonidou, Maria; Dasgupta, Abhijit
Abstract : Background: Sepsis is a serious infection that is often difficult to treat. We investigated if the risk of mortality in patients with systemic lupus erythematosus (SLE) hospitalized with sepsis varies among hospitals. Methods: We used the National Inpatient Sample (2002–2011) to obtain data on outcomes of adults age 18 to 64 with SLE who were admitted with a diagnosis of sepsis. We included 424 hospitals that had at least 5 hospitalizations of patients with SLE and sepsis. We abstracted data on demographic features, diagnoses, and mortality for these patients and for patients without SLE hospitalized with sepsis at the same set of hospitals. We used machine learning methods to derive the expected risk of in-hospital mortality for each patient, based on demographic features, insurance status, comorbidities, and diagnoses related to organ failure. We then computed the observed/expected ratio for in-hospital mortality separately for SLE and non-SLE patients by hospital. To further adjust for case-mix, the ratio of these two ratios (RR) was used to evaluate the relative likelihood of death among those with SLE compared to those without SLE at the same hospital. Results: We included 4001 hospitalizations of patients with SLE and sepsis, and 2 02 888 hospitalizations of patients with sepsis without SLE. The number of SLE hospitalizations ranged from 5 to 66 per hospital. Across all hospitals, 11.5% of patients with SLE and 13.1% of patients without SLE died during the hospitalization. The RR was greater than 1.0 in 44% of hospitals, and greater than 2.0 in 16% of hospitals, indicating increased risk of mortality by a factor of two or more among patients with SLE compared to those without SLE at the same hospital. Based on classification tree analysis, large urban hospitals were less likely to have RR >2 than smaller hospitals (13% vs 22%), particularly those in the midwest or northeast (35%). Conclusions: Risks of mortality due to sepsis among patients with SLE varied widely among U.S. hospitals. Risks were higher for patients with SLE at smaller hospitals. Acknowledgements: Supported by the Intramural Research Program, NIAMS/NIH.